Fraud Pentagon dalam Mendeteksi Kecurangan Laporan Keuangan - Audri Widiastika; Junaidi Junaidi (Penerbit Goodwood, 2022)
Purpose: The study aims to test the influence of pentagon fraud in detecting fraudulent financial statement. There are five concepts of pentagon fraud: pressure, opportunity, rationalization, capability and arrogance. Research methodology: This sample used is manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2019 with a total sample were 286. The Sampling techniques used purposive sampling, with multiple linear regression test. Results: The results of the analysis showed that the variables of financial stability, external pressure ? and financial targets statistically had a significant effect on fraudulent financial statement. However, other variable do not significantly affect fraudulent financial statement. Limitations: The study used the assumption that potential entity fraud was only detected with seven indicators. In addition, sampling is done by purposive sampling, so this next study needs to be done random sampling in order to reflect the entire population. Contribution: The results of this study are expected to test and develop the pentagon's fraud concept. In addition, users of financial statements are expected to be able to detect potential fraud of the entity's financial reporting.